Peran Self-Regulated Learning dalam Meningkatkan Hasil Belajar Fisika Siswa SMA: Kajian Meta-Analisis - Dewati, Maria; Bhakti, Yoga Budi; Soleha, Andini (UNIVERSITAS INDRAPRASTA PGRI, 2024)
This study aims to analyze the effect of Self-Regulated Learning (SRL) on the physics learning outcomes of high school students through a meta-analysis of national scientific publications. The approach used is a descriptive method with meta-analysis techniques applied to data from various studies implementing the SRL model. The analysis results show that the application of SRL has an effect with an average effect size of 0.252 (small category). Based on the education level, the effect size is 0.241 (small category). Based on regions, the highest effect sizes were found in Bali (0.485) and South Sumatra (0.665), both categorized as large effects. Regarding related variables, the general effect size of SRL is 0.221 (SD = 0.221; small to moderate category), while the effect size of SRL on learning outcomes is 0.261 (SD = 0.261; small to moderate category). These findings indicate that the implementation of SRL has a meaningful impact on improving physics learning outcomes among high school students.